Dimensions of Maqāṣid Al-Sharī‘ah and Human Rights in the Constitutional Court’s Decision on Marriage Age Difference in Indonesia - Purnomo, Agus; Salam, Nor; Zamzami, Mukhammad; Bakar, Abu (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This article analyzes the Constitutional Court's ruling on the difference in marriage age between men and women as contained in Decision Number 22/PUU-XV/2017 and examines whether the decision guarantees the protection of human rights. Methodologically, the study is a normative research using the maqāṣid al-sharī'ah approach and human rights as analytical tools. The data analyzed are Constitutional Court decisions, journal articles, books and various literature related to the discussion. The study concluded that the Constitutional Court's ruling on the age limit for marriage contains aspects of maqāṣid al-sharī'ah in the form of considerations to prevent harm. This is in line with the general rule in Islamic law of avoiding damage (mafsadah) which must take precedence over efforts to achieve benefit. Another aspect of maqāṣid in the Constitutional Court's ruling is that it affirms the protection of life (ḥifẓ al-nafs), either through the enforcement of qiṣāṣ (retributive justice) or the protection of children or minors. This legal principle can also mean protection from all forms of discrimination and violence, all of which are assessed in the ruling. Viewed from a human rights perspective, the ruling is closely related to the affirmation of discriminatory treatment of women, as the main objective of basic human rights and must be protected. However, this decision also cannot be interpreted as an equality of women with men. Gender differentiation does exist but should not result in harm.